Study on the Water-Physical Properties of the Cement-Plaster Bonded Rock-Like Materials - Yong Zhang; Zhiguo Cao; Xiaomeng Shi (Advances in Civil Engineering)
The cement-plaster bonded rock-like material is one of the most commonly used materials to simulate different rocks in physical model tests. However, the applicability of this material in solid-fluid coupling model tests is not clear because there are few research studies on the water-physical properties of this material and its similarity to the actual rock is uncertain. This paper presents a systemic experimental study on the water-physical properties of the cement-plaster bonded rock-like materials. The parameters of rock-like materials, including water absorption, softening coefficient, and permeability coefficient, were compared with those of actual rocks to analyse the applicability of such material. Then, the influence of proportion on the water-physical properties of this material was discussed. By multiple regression analysis of the test results, empirical equations between the water-physical parameters and proportions were proposed. The equations can be used to estimate the water-physical properties of cement-plaster bonded rock-like materials with specific proportion and thus to select suitable materials in the solid-fluid coupling physical model tests.